Evaluation of antidiabetic and antioxidative efficacy of ethyl acetate fraction of methanolic extract of Camellia sinensis (green tea) leaves in streptozotocin induced diabetic albino rat - Baisakhi Biswas; Barnali Das; Kishalay Jana; Debidas Ghosh (International Journal of Phytomedicine, 2017)
Objective: To investigate the antidiabetic and antioxidative potentiality of ethyl-acetate fraction of methanolic extract of Camellia sinensis (Green tea) leaves in streptozotocin induced diabetic rat. Methods: Streptozotocin induced diabetic state was confirmed by increased level of fasting blood glucose, decreased level of serum insulin along with inhibition in carbohydrate metabolomics. Oxidative stress was assessed by measuring antioxidative enzyme activities of hepatic and skeleto-muscular tissue. Hepatic Hexokinase-I, pro-apoptotic Bax and anti-apoptotic Bcl-2 gene expression patterns were noted by qRT-PCR technique. Results: After treatment with ethyl-acetate fraction of methanolic extract of Camellia sinensis (Green tea) leaves at a dose of 100 mg/kg body weight/day to diabetic rats for 28 days, a significant (p < 0.05) recovery was noted in fasting blood glucose level, serum insulin level along with activities of carbohydrate metabolic enzymes in hepatic tissue in respect to the vehicle treated diabetic group. This fraction also resulted a significant (p < 0.05) recovery in the activities of antioxidative enzymes in hepatic and skeleto - mascular tissue. In streptozotocin induced diabetic rat the low level of expression of Hexokinase-I, anti-apoptotic Bcl-2 and high level of expression of pro-apoptotic Bax gene were observed in hepatic tissue in respect to vehicle treated control. There were recovered significantly after the treatment with the said fraction. Conclusion: From the results, it may be concluded that ethyl-acetate fraction of methanolic extract of leaves of C. sinensis has a promising anti-diabetic and antioxidative activities for the management of streptozotocin induced diabetic state.